ORTOGRAFI ARAB DAN PROBLEMATIKANYA - Umi Nurun Ni’mah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
The old Arabic orthography contains some flaws. Besides having no different symbols to differentiate short and long vowels, it had no diacritics to differentiate the letters, which caused significant reading problems. Those problems became more complicated when it became the means in the process of writing the Qur’an since it caused errors in its recitation. In the post-Mohammedan period, when Islam was spread outside the Arabic lands, some non-Arabic Moslems had difficulties to read the Qur’an. Those problems concerned many scholars and urged them to find solution. Some efforts were done by inventing the reader-friendly orthographic system as it is well known today. This paper aims to discuss that topic. However, some new flaws emerged. The orthographic modifications which have been sufficient for writing needs to be developed and adapted to present demands. Some scholars have proposed some new ideas. Generally, these ideas can be grouped into two opposing views: firstly, those which preserve the existing orthographic tradition, pioneered by Emīl Badī’ Ya’qūb; secondly, those which go beyond it, suggesting almost total transformation, pioneered by Anīs Farīḥa. This paper also discusses their ideas as its second purpose. Based on different epistemological bases, the application of each idea will affect differently in learning/teaching as well as in Arabic religiosity and nationalism.